Valuation : measuring and managing the value of companies - Copeland, Thomas E., 1946-; Murrin, Jack.; Koller, Tim. (New York : Wiley, 2000)
Valuation provides insights into how to measure, manage, and maximize a company's value. This Third Edition has updated and expanded to reflect business conditions in today's volatile global economy and to provide highly effective ways for managers at every level to create value for their companies.
Includes index.
oif 13/03/15
Loan
Keywords: Corporations -- Valuation -- Handbooks, manuals, etc